TNF and ubiquitin at the crossroads of gene activation, cell death, inflammation, and cancer - Walczak, Henning (Immunological reviews, 2011)
Tumor necrosis factor (TNF) is crucial for innate immunity, but deregulated TNF signaling also plays an eminent role in the pathogenesis of many chronic inflammatory diseases and cancer‐related inflammation. The signals that mediate both the beneficial and the harmful effects of TNF are initiated when TNF binds to its receptors on the surface of target cells. TNF receptor 1 (TNFR1) is ubiquitously expressed, whereas TNFR2 is mainly expressed on lymphocytes and endothelial cells. This review focuses on the molecular and physiological consequences of the interaction of TNF with TNFR1. The different outcomes of TNF signaling originate at the apical signaling complex that forms when TNF binds to TNFR1, the TNFR1 signaling complex (TNF‐RSC). By integrating recently gained insight on the functional importance of the presence of different types of ubiquitination in the TNF‐RSC, including linear ubiquitin linkages generated by the linear ubiquitin chain assembly complex (LUBAC), with the equally recent elucidation of the mode in which ubiquitin‐binding domains interact with specific di‐ubiquitin linkages, this review develops a new concept for the way the concerted action of different ubiquitination events enables the TNF‐RSC to generate its signaling output in a spatio‐temporally controlled manner. Finally, it will be explained how these new findings and the emerging concept of differential ubiquitination governing the TNF‐RSC may impact future research on the molecular mechanism of TNF signaling and the function of this cytokine in normal physiology, chronic inflammation, and cancer.